Fuzzy logic for image processing : a gentle introduction using Java - Caponetti, Laura; Castellano, Giovanna (Springer, 2017)
"This book provides an introduction to fuzzy logic approaches useful in image processing. The authors start by introducing image processing tasks of low and medium level such as thresholding, enhancement, edge detection, morphological filters, and segmentation and shows how fuzzy logic approaches apply. The book is divided into two parts. The first includes vagueness and ambiguity in digital images, fuzzy image processing, fuzzy rule based systems, and fuzzy clustering. The second part includes applications to image processing, image thresholding, color contrast enhancement, edge detection, morphological analysis, and image segmentation. Throughout, they describe image processing algorithms based on fuzzy logic under methodological aspects in addition to applicative aspects. Implementations in java are provided for the various applications"--Provided by publisher.
Keywords: Fuzzy logic.; Image processing -- Digital techniques.; Java (Computer program language); elektronické knihy; electronic books